Content analysis of the existence of biomimicry life’s principles in green building index Malaysia - Hj Mohd Ariffin, Noor Aziah; Gad, Salwa Farag (Malaysian Institute of Planners, 2017)
Concerns about climate change and global warming have led many countries to initiate energy rating systems in the planning and development of the built environment. Although useful and novel, this paper contends that these ratings are only remedying and alleviating whatever negative impacts that development creates. Energy ratings are seemingly lacking in attempts to integrate and enhance the physical development of the natural environment. Instead, Biomimicry is a discipline that explores nature and tries to understand its bio-integration for the establishment of sustainable products, processes and systems. This paper postulates that with the integration of Biomimicry – Life’s Principles (BLP) into the Green Building Index (GBI) Malaysia, a higher level of environmental sustainability could be achieved. This paper attempted to explore the presence and the extent of the presence of BLP in the existing GBI utilizing the content analysis method. This article concludes that although the presence of BLP in the GBI is high, the extent of the presence is low. The paper also recommends the areas of concern that could be improved within the GBI for a more effective rating system.